Answer:
6 (y + 8) (y - 1)
Step-by-step explanation:
Factor the following:
6 y^2 + 42 y - 48
Factor 6 out of 6 y^2 + 42 y - 48:
6 (y^2 + 7 y - 8)
The factors of -8 that sum to 7 are 8 and -1. So, y^2 + 7 y - 8 = (y + 8) (y - 1):
Answer: 6 (y + 8) (y - 1)
PS: it's really helpful to pose the question correctly 6 y^2 + 42 y - 48 NOT
6y 2 - 48 + 42y
Answer:
$2.83
Step-by-step explanation:
Diameter of the pool = 24ft
Cost of 1 ft² = $0.15
Area of the pool=?
But the pool is a circular pool,
Area of a circle = Πr² or πd²/4
π = 3.142
Area of the pool = (π * 24) / 4
Area = (3.142 * 24) / 4
Area = 18.85ft²
If 1ft² = $0.15
18.85 = $x
x = (18.85 * 0.15) / 1
x = $2.8275 = $2.83
The cost of the pool is $2.83
Answer is the third one. It is the only answer where all points work in the equation.
Answer: third choice